2020
DOI: 10.1186/s12868-020-00566-4
|View full text |Cite
|
Sign up to set email alerts
|

Conformity-like behaviour in mice observing the freezing of other mice: a model of empathy

Abstract: Background: Empathy refers to the ability to recognise and share emotions with others. Several research groups have recognised observational fear in mice as a useful behavioural model for assessing their ability to empathise. However, in these observation systems, it remains unclear whether the observer mouse truly recognises the movements of, and empathises with, the demonstrator mouse. We examined changes in the behaviour of an observer mouse when a demonstrator mouse was anaesthetised, when the demonstrator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Our results provide additional evidence that mice can rapidly and reliably adopt the sensory-affective state of a social partner, regardless of the valence of the information (pain, fear, or pain relief). Although it is conceivable that the behavioral responses of our BY mice reflect “imitative” or “mimicry” behavior ( 45 ) rather than “empathy,” several findings suggest that at least for the social transfer of pain and analgesia, the BY mice manifest changes in their behavior because they are experiencing an altered sensory-affective state. Importantly, the BY mice were tested using several different behavioral assays and did not always have direct visual access to their social partners during testing.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide additional evidence that mice can rapidly and reliably adopt the sensory-affective state of a social partner, regardless of the valence of the information (pain, fear, or pain relief). Although it is conceivable that the behavioral responses of our BY mice reflect “imitative” or “mimicry” behavior ( 45 ) rather than “empathy,” several findings suggest that at least for the social transfer of pain and analgesia, the BY mice manifest changes in their behavior because they are experiencing an altered sensory-affective state. Importantly, the BY mice were tested using several different behavioral assays and did not always have direct visual access to their social partners during testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the experiment of Rice (1964), it was not clear whether this effect and the observers' fear‐related responses were due to the features of the apparatus or triggered by the sight of the distressed conspecific.Some recent and more controlled studies have provided mixed results on the response of rodents to the exposure of conspecifics being subjected to physical stressors. Four studies showed that neither the visual (Sanders et al, 2013) nor auditory (Atsak et al, 2011; Chen et al, 2009; Ueno et al, 2020) exposure to familiar or unrelated conspecifics receiving foot‐shocks or to videos of foot‐shocked cagemates elicited freezing responses in observer rodents. However, another series of studies provided positive evidence of this phenomenon.…”
Section: Studies On Emotional Contagion In Nonhuman Animalsmentioning
confidence: 99%
“…(Allsop et al, 2018; Atsak et al, 2011; Carrillo et al, 2015; Chen et al, 2009; Gonzalez‐Liencres et al, 2014; Jeon et al, 2010; Jeon & Shin, 2011; Keum et al, 2016; Keum et al, 2018; Pisansky, Young, et al, 2017; Pisansky, Hanson, et al, 2017; Sanders et al, 2013; Ueno et al, 2020; Ueno et al, 2020 ( video) ) (Sehoon Keum et al, 2018)…”
Section: Main Findings and Problems In The Study Of Emotional Contagion In Nonhuman Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental environment without dividers, we investigated whether the nature of the demonstrator in the adjacent transparent cylinder changed the depressive-like behaviour of the test subjects, since it has been shown that mice change their behaviour by imitation of other individuals 34 39 . However, in this experiment, the behaviour of the cage mate in the adjacent cylinder, irrespective of whether they were hyperactive or immobile, did not change the behaviour of the observer.…”
Section: Discussionmentioning
confidence: 99%